Mechanical properties and microstructure of pre-treated luffa fiber reinforced cement mortar - Renqiang Yang; Zhengjun Guan; Lihua Zhang; Yong Shu (PLoS ONE, 2025)
In this work, leveraging the enhanced wear resistance, toughness, and renewability of luffa fiber, pretreated luffa fiber was applied into cement mortar to investigate the impact of different fiber contents and sizes on mortar performance. Meanwhile, the fiber-mortar interface fusion and hydration products were systemically analysed by performing SEM-EDS (scanning electron microscopy-energy spectrum analysis) and CT (Computed Tomography) tomography measurements. From our analysis, it was demonstrated that pretreated luffa fibers could significantly enhance the strength, shrinkage resistance, and toughness of cement mortar. When the fiber content was 1% and the length was 1 cm, the 28-day compressive and flexural strengths of the cement mortar reached 57.63 MPa and 9.68 MPa, respectively, representing an increase of 10.81% and 9.47% compared to ordinary cement mortar. When the fiber content was 1%, with fiber lengths of 1 cm and 2 cm, the 56-day drying shrinkage rates of the cement mortar were 2.78% and 6.09%, respectively. This result corresponds to a reduction in shrinkage by factors of 7.17 and 3.27, respectively, compared to standard cement mortar. Additionally, with a fiber content of 1% and lengths ranging from 1 to 3 cm, the load-deflection behaviour of luffa fiber cement mortar was noticeably superior to that of conventional mortar. The SEM-EDS images revealed that cement mortar containing 1 cm fibers had a substantial presence of tinfoil-like C-S-H (hydrated calcium silicate) and needle-like AFt (ettringite) structures. In addition, better integration with the cement mortar compared to other fiber lengths was demonstrated. CT tomography showed that luffa fibers were concentrated in large amounts at the top and bottom of the test samples, with an increase in voids and fiber agglomeration as the fiber content increased. In summary, when the luffa fiber content was 1% and the fiber length was 1 cm, the mechanical performance of cement mortar could be effectively enhanced and fiber agglomeration can be mitigated, suggesting potential applications in building materials.